Analisis Pengaruh Program Bantuan Pangan Non-Tunai (BPNT) dan Program Keluarga Harapan (PKH) Terhadap Kemiskinan - Friska Olabu; Sri Endang Saleh; Sri Indriyani Dai (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to analyze the effect of the Non-Cash Food Assistance Program (BPNT) and the Family Hope Program (PKH) on poverty (case study in Tenilo Village, West City District, Gorontalo City). The data used in this study are primary data sourced from 81 respondents. This research uses Multiple Linear Regression Analysis. The results of this study indicate that 1). Non-Cash Food Assistance (BPNT) has a negative and significant effect on Poverty in Tenilo Village. This means that every increase in Non-Cash Food Assistance can reduce Poverty in Tenilo Village, West Kota District, Gorontalo City. 2). The Family Hope Program (PKH) has a negative and significant effect on Poverty in Tenilo Village. This means that every increase in the Family Hope Program (PKH) can reduce poverty in Tenilo Village, West Kota Subdistrict, Gorontalo City. 3). Non-cash Food Assistance (BPNT) and the Family Hope Program (PKH) have a simultaneous effect on Poverty in Tenilo Village.